计算:3×2÷2-2×6÷3÷3+5-3=______.
1个回答
3×2÷2-2×6÷3÷3+5-3,
=6÷2-12÷3÷3+5-3,
=3-4÷3+5-3,
=3-
4
3 +5-3,
=
5
3 +5-3,
=
20
3 -3,
=
11
3 ,
=3
2
3 .
故答案为:3
2
3 .
相关问题
简便计算 19.3÷50÷2 360÷(3+1.8) 3.4×12.5+6.6×12.5 2.6÷0.25÷0.13 2
规定a☆b=3a-2b,如6☆5=3×6-2×5=8,请计算:(5÷3☆3÷4)☆4÷3
计算下列题 2 3 ×( 3 8 + 5 6 ) 75%× 5 12 ÷2.5 5 14 ÷ 2 3 - 3 7 × 5
3×(-9)+7×(-9) (5/4-7/6)×(-8/7) (-54)÷6÷(-3) (-54)÷6÷(-3) 2×{
计算:(1)-3+5×(-4)-12÷(-3)(2)(13−34+56)÷(−112)(3)−12012−6÷3×13(
计算下面各题:5/14÷20/21×3/4 [2-(1/2-1/3]×6/5= == == =5/6÷3/4+1/6÷3
计算-0.3²÷0.5×2÷(-2)³=
1+1×2+2×3+3×4+4÷5+5÷6+6÷7+7÷8+8÷9+9÷10+10=?
简算1÷(1×2×3)+1÷(2×3×4)+1÷(3×4×5)+1÷(4×5×6)+.+1÷(98×99×100)
计算:(1)(-12)÷4×(-6)÷2;(2)(−58)×(−4)2−0.25×(−5)×(−4)3;(3)(−112